1992
DOI: 10.1002/ajmg.1320430625
|View full text |Cite
|
Sign up to set email alerts
|

VACTERL or MURCS association in a girl with neurenteric cyst and identical thoracic malformations in the father: A case of gonosomal mosaicism?

Abstract: We report on a female infant with lethal congenital malformations including extreme hydrocephalus due to aqueductal stenosis, vertebral segmentation anomalies, fused costae, anal atresia, renal dysplasia, and bicornuate uterus with a double blind vagina. The VACTERL and the MURCS associations are possible diagnoses. Her father had a neurenteric cyst in infancy. He has identical vertebral and costal malformations as his daughter but is otherwise healthy. The possibility of dominant inheritance with gonosomal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…There are also data indicating the involvement of the CNS. Extreme hydrocephalus due to acqueduct stenosis (Orstavik et al 1992), cerebellar cyst and heterotopia of Purkinje and granule cells in the cerebellar cortex in the vicinity of the cyst (Greene et al 1986) and occipital encephalocele (Suri et al 2000, Lin et al 1996) have been reported. In an autopsy study of a stillborn female infant of 41 weeks gestation, Lin and colleagues reported the presence of polymicrogyral formation in both hemispheres; small midbrain, pons and cerebellum besides an occipital encephalocele (Lin et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…There are also data indicating the involvement of the CNS. Extreme hydrocephalus due to acqueduct stenosis (Orstavik et al 1992), cerebellar cyst and heterotopia of Purkinje and granule cells in the cerebellar cortex in the vicinity of the cyst (Greene et al 1986) and occipital encephalocele (Suri et al 2000, Lin et al 1996) have been reported. In an autopsy study of a stillborn female infant of 41 weeks gestation, Lin and colleagues reported the presence of polymicrogyral formation in both hemispheres; small midbrain, pons and cerebellum besides an occipital encephalocele (Lin et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with at least three major defects are diagnosed as having VATER association. However, there are several other congenital syndromes, including the Goldenhar syndrome [5], the coloboma, heart disease, atresia choanae, retarded growth and development, genital hypospadia, and ear anomalies/deafness (CHARGE) syndrome [13,16], the mullerian duct aplasia, renal aplasia and cervicothoracic somite dysplasia (MURCS) association [15], the HoltOram syndrome (cardiac and forelimbs anomalies) [6], and the omphalocele, exstrophy, imperforate anus, and spinal defects (OEIS) complex [3], which have manifestations overlapping those of the VATER association. These types of patients may even be described as special forms of VATER associations [22], although some authors have discouraged the extension of the term VA-TER to encompass a wide spectrum of different diseases of diverse aetiologies in the association [20].…”
Section: Discussionmentioning
confidence: 99%
“…Hierzu zählen u. a. das kaudale Regressionsyndrom, das Rokitanzky-Syndrom, die MURCS-Assoziation, die Fanconi-Anämie, das Holt-Oram-Syndrom, das Townes-Brocks-Syndrom und auch das TAR-Syndrom. Lurie und Ferencz weisen darauf hin, dass auch bei der VACTERL-H-Assoziation andere Syndrome, die ähnliche Symptome aufweisen können berücksichtigt werden müssen wie zum Beispiel das Baller-Gerold-Syndrom und das Steinfeld-Syndrom [26,27,28,29,30,31,32]. Evans et al stellten fest, dass unilaterale Defekte häufiger bei sporadischen Fällen einer VACTERL-Assoziation gefunden werden wie im Fall 1 zu vermuten ist.…”
Section: Diskussionunclassified